Misdiagnosis of scrub typhus complicated by hemophagocytic syndrome - Miaomiao Lin; Airong Huang; Xiang Zheng; Lisha Ge; Shijun He (BMC Pediatrics, 2019)
Abstract Background This study sought to analyze the cases of clinical misdiagnosis of scrub typhus complicated by hemophagocytic syndrome. Methods We retrospectively reviewed the medical records for diagnoses, clinical course, chest X-ray findings, laboratory data, and antibiotic therapy. Results All nine patients were misdiagnosed at the outpatient department between 07/2009 and 07/2017. They were diagnosed with septicemia and hemophagocytic syndrome, sepsis and hemophagocytic syndrome, severe infection, hepatitis and hemophagocytic syndrome, or upper respiratory tract infection. Among the nine patients, hepatic function examination showed decreased albumin and elevated C-reactive protein levels in all patients; alanine aminotransferase was increased and platelets were decreased in eight patients. Weil-Felix reaction was positive in three of nine patients. Indirect immunofluorescence demonstrated positive IgM antibody and EB virus-IgM in all nine patients; Mycoplasma pneumoniae antibody was positive in seven patients. All nine patients underwent chest computed tomography; no abnormality was found in two patients. Patch shadow with increased density was found in seven patients, including four patients with right pleural effusion and two with bilateral pleural effusion. Bone marrow biopsy was performed in all nine patients and hemophagocytic cells were seen. The nine misdiagnosed cases were given multiple broad-spectrum antibiotics either successively or concomitantly before and after admission, but no effective antibiotics against Orientis tsutsugamushi were applied. After diagnosis was corrected to scrub typhus, five patients were switched to chloramphenicol and dexamethasone, two patients were given azithromycin and dexamethasone, and two patients were treated with chloramphenicol. Body temperature returned to normal within 2–3 days and the children were quickly relieved from their condition. Conclusion Hemophagocytic syndrome may be the presenting clinical feature of scrub typhus and initially mask the disease. Initial misdiagnosis is common and includes septicemia and hemophagocytic syndrome. The eschar is a useful diagnostic clue and febrile patients without any localizing signs should be thoroughly examined for its presence.